Frequent occurrence of postbreakfast syncope due to carotid sinus syndrome after surgery for hypopharyngeal cancer: A case report. Issue 20 (21st May 2021) - Ando, Yuya; Hashimoto, Kenichi; Sano, Azusa; Fujita, Naoya; Yanagawa, Rempei; Ono, Yosuke; Obuchi, Yasuhiro; Tatsushima, Daisuke; Watanabe, Shun; Tomifuji, Masayuki; Tanaka, Yuji
Abstract: Rationale: Syncope often occurs in patients with advanced head and neck cancers due to the stimulation of the autonomic nervous system by the tumor. Here, we describe a case of frequent syncopal episodes after laryngopharyngectomy for hypopharyngeal cancer. As all syncopal episodes were observed during the forenoon, we also evaluated the heart rate variability using ambulatory electrocardiography to determine why the syncopal episodes occurred during a specified period of the day. Patient concerns: A 73-year-old Japanese man who underwent laryngopharyngectomy for recurrent hypopharyngeal cancer started experiencing frequent episodes of loss of consciousness that occurred during the same time period (10:00–12:00). He had never experienced syncopal episodes before the operation. From 23 to 41 days postoperatively, he experienced 9 syncopal episodes that occurred regardless of his posture. Diagnoses: Pharyngo-esophagoscopy revealed an anastomotic stricture between the free jejunum graft and the upper esophagus. Swallowing videofluoroscopy confirmed the dilatation of the jejunal autograft and a foreign body stuck on the oral side of the anastomosis. Contrast-enhanced computed tomography revealed that the carotid artery was slightly compressed by the edematous free jejunum. The patient was diagnosed with carotid sinus syndrome (CSS) as the free jejunum was dilated when consuming breakfast, which may have caused carotid sinus hypersensitivity and induced a medullary reflex. Interventions: Administration of disopyramide was effective in preventing syncope. Heart rate variability analysis using ambulatory electrocardiography showed that parasympathetic dominancy shifted to sympathetic dominancy during 10:00 to 12:00. The significant time regularity of the syncopal episodes may have been affected by modified diurnal variation in autonomic tone activity. Outcomes: After the surgical release and re-anastomosis of the pharyngoesophageal stenosis via an open-neck approach, no recurrent episodes of syncope were reported. Lessons: We reported a case of frequent syncopal episodes limited to the forenoon due to CSS after surgery for hypopharyngeal carcinoma. The patient was treated with anticholinergics followed by the release and re-anastomosis of the pharyngoesophageal stenosis. When syncope occurs after surgery for head and neck lesions, CSS due to postoperative structural changes should be considered as a differential diagnosis of syncope.